Self-Induced Fault of a Hydraulic Servo Valve A Possible Cause for Hidden Malfunction of Aircraft's Systems - Seung, Taehun; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This report describes recent trouble-shooting results in aircraft engineering concerning a self-induced fault mechanism of a hydraulic servo-valve. It presents a possible root cause for past aircraft accidents and as such helps to avoid such malfunction and its fatal consequences in the future.
Introduction -- Topics and arrangement of this report -- Occasion for investigation, brief description of the occurrence -- Appraisal and fundamental contemplation for a pressure controlling servo valve -- Existence of a self-induced fault of a two stage servo valve - Hypothesis -- Experimental investigation - Test execution and results -- Reconstruction of the entire fault working mechanism - interim conclusion -- Additional reflections / Supplementation of contemplation -- Conclusion.
Keywords: Aerospace engineering; Astronautics; Machinery; Fluid mechanics; Aerospace Technology and Astronautics; Machinery and Machine Elements; Engineering Fluid Dynamics